2016
DOI: 10.1177/1557988316658640
|View full text |Cite
|
Sign up to set email alerts
|

Lisdexamfetamine Dimesylate (Vyvanse) for the Treatment of Neurogenic Anejaculation

Abstract: We report the first successful pharmacologic treatment of neurogenic anejaculation with lisdexamfetamine dimesylate (Vyvanse) in a 22 year-old Caucasian male with a history of pediatric pelvic neuroblastoma. At 2 years of age, the patient was found to have a pelvic mass abutting the sacrum and iliac vessels. Surgical excision required dissection along the sacral prominence and sacral nerve roots. He did not undergo chemotherapy or radiation as part of his treatment course for neuroblastoma. The patient was ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Despite the sparse literature on the effect of lisdexamfetamine on early ejaculation, we expected that compared to placebo, dimensions of early ejaculation would improve after regular intake of lisdexamfetamine during four consecutive weeks, and data did partially confirm this assumption. As such, the present data confirmed what has been observed in a case study of a 22-year-old Caucasian male with a history of pediatric pelvic neuroblastoma who suffered from anejaculation and aspermia with normal sensation of climax [ 28 ]: 60 mg of lisdexamfetamine dimesylate two hours before masturbation led to an antegrade ejaculate.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Despite the sparse literature on the effect of lisdexamfetamine on early ejaculation, we expected that compared to placebo, dimensions of early ejaculation would improve after regular intake of lisdexamfetamine during four consecutive weeks, and data did partially confirm this assumption. As such, the present data confirmed what has been observed in a case study of a 22-year-old Caucasian male with a history of pediatric pelvic neuroblastoma who suffered from anejaculation and aspermia with normal sensation of climax [ 28 ]: 60 mg of lisdexamfetamine dimesylate two hours before masturbation led to an antegrade ejaculate.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study we focused on the influence of lisdexamfetamine dimesylate on early ejaculation for the following two reasons. First, Lyons et al [ 28 ] reported in their case study that a 22 year-old Caucasian male with a history of pediatric pelvic neuroblastoma suffered from anejaculation and aspermia with normal sensation of climax. When the patient took lisdexamfetamine dimesylate 60 mg two hours prior to masturbation, he produced an antegrade ejaculate with the first use of the medication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts have been made to treat DE/AE using off-label medications based on pharmacological and physiologic considerations [ 91 92 93 ]. However, an approved drug does not exist.…”
Section: Treatmentmentioning
confidence: 99%
“…Of interest is the recent single-case report of the successful oral administration of 60 mg of lisdexamfetamine dimesylate (a prodrug that is converted by the liver to the active dextroamphetamine. which is a noncatecholamine, sympathomimetic amine) 2 hours prior to masturbation in a patient with neurogenic AE [ 92 ]. In contrast, a recent double-blind randomized placebo-controlled small study [ 94 ] showed that midodrine was similar to placebo in inducing antegrade ejaculation in patients with SCI.…”
Section: Treatmentmentioning
confidence: 99%